Analysis and Research of the High-Cycle Fatigue Fracture Mode Based on Stress Ratio and Residual Stress of Ti-6Al-4V. (12th January 2022) - Wang, Fu; Wang, Jian-Jun; Li, Qin-Sheng; Ren, Guo-Zhu; Zhang, Xin-Jian; Zhang, Shu-quan
Abstract : The content of titanium is about 0.63% in the earth's crust, and it ranks 10th among all elements. The content of titanium is next to the metal elements of aluminum, iron and magnesium, iron, and magnesium; titanium alloys have low density, high specific strength (the ratio of tensile strength to density), wide working range (−253°C–600°C), and excellent corrosion resistance melting point; the chemical activity of titanium alloy is very high, and it easily reacts with hydrogen, oxygen, and nitrogen, so it is difficult to be smelted and processed, and the processing cost is high. Titanium alloys also have poor thermal conductivity (only 1/5 of iron and 1/15 of aluminum), small deformation coefficient, large friction coefficient, and other characteristics. They are widely used in aircraft fuselage, gas turbine, petrochemical, automotive industry, medical, and other fields for important parts.